Proceedings of the seminar: PLANLAC and the media - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
224 páginas. Series Reports, Results and Recommendations of Technical Events A2/TT (IICA) no. 92-001.